Efficacy of two inducing agents PG and DoM+SGnRH in the induced breeding of the major carp, kalibaus (Labeo calbasu) - Ahktar, Jesmin; Bhuiyan, Abdus Salam (University Journal of Zoology, Rajshahi University, 2013)
An experiment on the induced breeding of the endangered fish, Labeo calbasu (Hamilton-Buchanam) was conducted in the Fish Seed Multiplication Farm,Rajshahi to know the efficacy of two inducing agents (PG and DoM+SGnRH). Three breeding trials of each inducing agent were performed. A total of 24 females weighing from 1.5 kg to 2 kg were given an initial and a resolving dose of 1.5 mg and 6 mg PG extract per kg body weight respectively as treatment-1. On the other hand, a total of 24 females weighing from 1.5 kg to 2 kg were given a single dose of 12 mg DoM + SGnRH/kg as treatment-2. In case of treatment-1, 12 males weighing from 1.5 kg to 1.95 kg were administered a single dose of 1.5 mg PG/kg body weight during resolving dose of female. In treatment-2, 12 males weighing from 1.5 kg to 1.8 kg were administered 3 mg DoM+SGnRH /kg body weight during initial dose of females. In treatment-1, the time interval between initial and resolving dose was 5 hours and ovulation occurred in all the injected females within 6 hours after resolving dose. Ovulation occurred within 6 to 8 hours after the injection of inducing agents for treatment-2. The mean rates of ovulation, fertilization and hatching were 100%, 77.36% and 74.5% respectively in treatment-1. On the contrary, the mean rates of ovulation, fertilization and hatching were 83.33%, 63.83% and 59.66% in treatment-2. Hatchery produced fry were reared in nursery pond for 40 days. In nursery pond. Flour, oil cake and wheat bran were applied as nursery feeds. Both the inducing agents were effective in respect of overall breeding performance. But the best results were obtained with PG although in case of DoM+SGnRH complete breeding takes place within short time with less labour and cost than that of PG. DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15376 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 23-26